Integration and trends of technology IR 4.0 In Malaysian education system - Ngatiman, Suriani; Sulaiman, Tajularipin; Kai, Yan Wong (Kalahari Journals, 2022)
This current study aims to identify the trends in the use of IR4.0 technology activities implemented in the Malaysian education. The research methodology is based on the PRISMA model (Preferred, Reporting Items for Systematic Reviews and Meta-Analysis) which is used as a method of obtaining data analysis using the main electronic databases namely Web of Science (WoS) and Scopus. A comprehensive survey through data analysis has found 23 studies on IR4.0 technology in the publication period between 2018 to 2020 implemented in education context of studies in Malaysia based on the specified criteria. IR4.0 technology activities as teaching aids in teaching and learning are more implemented than as a syllabus that needs to be learned. While the level of education that integrates IR4.0 technology is dominated by higher education institution through the involvement of lecturers, students and administration compared to teachers and school students. The field of Engineering and Computer Science is ahead of other fields. The study was synthesized using ATLAS.ti 8 software based on general characteristics such as how activities using IR4.0 technology were integrated, level of education, and field of education were implemented as well as the potential integration of IR4.0 technology to the Malaysian education system. Some suggestions for future scholars will be discussed at the end of this study.